If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(t + -8) + -1(t + 8) = 3 Reorder the terms: -9(-8 + t) + -1(t + 8) = 3 (-8 * -9 + t * -9) + -1(t + 8) = 3 (72 + -9t) + -1(t + 8) = 3 Reorder the terms: 72 + -9t + -1(8 + t) = 3 72 + -9t + (8 * -1 + t * -1) = 3 72 + -9t + (-8 + -1t) = 3 Reorder the terms: 72 + -8 + -9t + -1t = 3 Combine like terms: 72 + -8 = 64 64 + -9t + -1t = 3 Combine like terms: -9t + -1t = -10t 64 + -10t = 3 Solving 64 + -10t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-64' to each side of the equation. 64 + -64 + -10t = 3 + -64 Combine like terms: 64 + -64 = 0 0 + -10t = 3 + -64 -10t = 3 + -64 Combine like terms: 3 + -64 = -61 -10t = -61 Divide each side by '-10'. t = 6.1 Simplifying t = 6.1
| 7(6x+4)+2=42x+30 | | -4y+6=-2(4y+5) | | r=4k+4w | | X^2+10=2 | | 9x-3=9(x-2) | | 3(x-5)=2(x+2) | | 7+9(x-8)=10-3(x-5) | | X^2+2x-324=2x | | 3/4(x-7)=x+2 | | 11x^2+x-2=0 | | 0=(21x)(21x)-2x-40 | | 5x^2-16=-x^2+80 | | 12x^2+11x-5=0 | | x/6+5=x/6 | | 6(n+7)=2(21+3n) | | 5y-10=7(2y-3)+14-9y | | 9p^2+6p-8=0 | | 4x-y=21 | | 0.30x+0.25(30)=0.15(106) | | 3x^2-16x=x^2-30 | | x^2+6x-21=0 | | 5y-3=5(y-1) | | 2x+3=2y | | 6t=48 | | x-2x=3x-27 | | -4(8+5)=8 | | 7k=k-18 | | 49x=245 | | y=-20sin(4x) | | -3y-10=6y+17 | | -10v+2=-70 | | 2x-2y=3 |